Towards the total synthesis of keramaphidin B - Jakubec, Pavol (Beilstein J Org Chem, 2016)
The enantio- and diastereoselective Michael addition of a δ-valerolactone-derived pronucleophile to a substituted furanyl nitroolefin catalysed by a bifunctional cinchonine-derived thiourea has been used as the key stereocontrolling step in a new synthetic strategy to the heavily functionalised piperidine core of keramaphidin B.